Poultry Effluent Bio-treatment with Spirodela intermedia and Periphyton in Mesocosms with Water Recirculation - Basílico, Gabriel Omar (2016)
Abstract: Industrial production of poultry meat is associated with indirect environmental impacts such as contributing to climate change and deforestation and otherdirect impacts such as the deterioration of the quality ofsurface waters. Poultry industry effluents are rich inorganic matter, nitrogen, and phosphorus; nutrients canbe removed from wastewater through the use of macrophytes and periphyton. An essay in mesocosms withpoultry industry wastewater recirculation was developed in the presence and absence of a native macrophyteSpirodela intermediaand periphyton from a lowlandstream (La Choza stream, Buenos Aires) where theeffluent is poured. The diffusion of O2,increasedbywater recirculation, had the effect of increasing theconcentration of dissolved oxygen in wastewater. Thepresence ofS. intermediaand algae periphyton significantly contributed to the removal rates (%) of solids(69.7 ± 3.9), ammonium nitrogen (84.0 ± 3.4), and totalphosphorus (38.1 ± 1.8) from residual water and favorednitrification. The dominance of Bacillariophyceae onother groups of algae of periphyton and the low representation of Euglenophyceae indicated an advancedstage of the effluent treatment process at the end of theassay.